2012
DOI: 10.1038/leu.2012.329
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-alpha is a therapeutic target for chronic lymphocytic leukemia

Abstract: Chronic lymphocytic leukemia (CLL) cells with aggressive clinical properties express lipoprotein lipase (LPL), which generates activating ligands for the nuclear receptor peroxisome proliferator activated receptor (PPAR)α and allows fatty acids to be used as fuel. However, the role of PPARα in CLL is unclear. PPARα was found to be expressed by circulating CLL cells and highly associated with advanced stage disease. Consistent with this observation, palmitate oxidation rates in circulating CLL cells were simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 35 publications
3
80
0
Order By: Relevance
“…PPARα was previously shown to mediate protection of CLL cells from harsh microenvironmental conditions, including the presence of cytotoxic agents (23,30). This result suggests that PPARα plays a role in CLL cell viability.…”
Section: Pparα Antagonist Is Cytotoxic To Cll Cells Even In the Presesupporting
confidence: 58%
See 4 more Smart Citations
“…PPARα was previously shown to mediate protection of CLL cells from harsh microenvironmental conditions, including the presence of cytotoxic agents (23,30). This result suggests that PPARα plays a role in CLL cell viability.…”
Section: Pparα Antagonist Is Cytotoxic To Cll Cells Even In the Presesupporting
confidence: 58%
“…Spaner et al (23) showed that PPARα expression was highly associated with advanced-stage disease. Thus, PPAR expression could be used to select the patient population that would benefit from treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations